A novel dual-layer approach towards omniphobic polyurethane coatings. Issue 46 (27th August 2019) - Khan, Fahad; Khan, Ajmir; Tuhin, Mohammad O.; Rabnawaz, Muhammad; Li, Zhao; Naveed, Muhammad
Abstract : Omniphobic surfaces have a plethora of applications ranging from household paints to sensors. Abstract : Omniphobic surfaces have a plethora of applications ranging from household paints to sensors. The predominant practice of fabricating those materials/surfaces is to use fluorinated materials which are environmentally harmful, and thus have limited practical applications. In this study, we report a novel dual-layer approach of fabrication towards omniphobic surfaces using polyurethane (PU) as a matrix and polydimethylsiloxane (PDMS) as a self-cleaning ingredient. This approach was also used to produce omniphobic PU nanocomposites, where nanofillers ( e.g., nanoclay, cellulose nanocrystals (CNCs) and graphene oxide (GO)) were incorporated. The resultant coatings were investigated for their performance, such as optical clarity, durability, and self-cleaning properties. In addition, scanning electron microscopy (SEM) was used for microstructural analysis of the obtained coatings. The facile nature of fabrication and the use of PDMS, an environmentally benign material relative to fluorinated chemicals, thus offer an eco-friendly sustainable scheme for practical applications aimed at omniphobic purposes.